Enhancing Islamic Economics Students’ Vocabulary Proficiency and Creative Thinking through Video Project - Ariani, Desti; Jayanti, Ade Dwi; Hidayat, Ade; Putri, Riza Eka (LPPM Politeknik Raflesia, 2025)
This classroom action research aims to portray the improvement on student’ vocabulary proficiency and creative thinking through video project learning. The research was conducted to the first-semester students of the Islamic Economics Study Program of IAIN Curup. Observation and interview were used to collect the data. Observation on the video was on two purposes. First, to collect the data about English vocabulary used by the students to describe students’ vocabulary proficiency. Second, to collect the data on the performance of the video as a whole to analyze students’ creative thinking. The interview, in addition, was conducted to the students to gain a deeper understanding of the creative thinking process the students went through to complete the video project. The results of the study indicate that in terms of vocabulary, students' ability still needs improvement. Meanwhile, in terms of creative thinking in creating the video, students have demonstrated good creative thinking skills.